Tata Kelola Kolaboratif Ekowisata Berbasis Masyarakat Adat dalam Mewujudkan Pariwisata Berkelanjutan di Kasepuhan Karang, Kabupaten Lebak - Agustin Amalia; Jumanah Jumanah (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Indigenous community-based ecotourism requires governance that can balance economic benefits, cultural preservation, environmental conservation, and the authority of local institutions. This study aims to analyze collaborative governance in indigenous community-based ecotourism to support sustainable tourism in Kasepuhan Karang, Lebak Regency. The study uses a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, field observation, document review, and limited discussions involving customary leaders, village government, local government agencies, local communities, academics, and supporting tourism actors. The data were analyzed using an interactive model consisting of data reduction, data display, conclusion drawing, and thematic analysis. The findings show that Kasepuhan Karang has strong ecotourism capital through local wisdom, customary forest management, cultural rituals, traditional knowledge, and community participation. However, its development still faces several constraints, including weak coordination among actors, limited human resource capacity, insufficient integration between formal policies and customary rules, and potential risks of environmental pressure and cultural commercialization. Collaborative governance is therefore essential to strengthen the roles of customary institutions, government, SABAKI, tourism awareness groups, academics, and local communities in planning, implementation, monitoring, and benefit sharing. This study recommends an indigenous community-based ecotourism governance model that emphasizes institutional collaboration, ethnoecological protection, local capacity building, destination carrying capacity control, and tourism product innovation aligned with customary values and sustainability principles.